China, India and industrial policy for inclusive growth - Inderjit N. Kaur; Nirvikar Singh (University of California, Economics Department, 2013)
This paper discusses a possible case for industrial policy, with special reference to the two emerging global giants, China and India. It begins with a clarification of the meaning of industrial policy, since not only does the term mean different things to different people, but the traditional and narrow definitions leads to significantly different conclusions than more recent, broader definitions. In the context of definition of the term, the paper also reviews the arguments for and against industrial policy, and discusses industrial policy in the context of globalization, including the evolution of multilateral trading rules. The main arguments of the paper discuss the Chinese and Indian economies, exploring in particular their past experience with variants of industrial policies. The similarities of the China model to past East Asian experience are explored, while the contrasts of India's development, and the distinction between liberalization and reform are examined. These two major country cases form the basis for a consolidation of recent conceptual ideas, where effective and successful industrial policy is viewed as part of a social contract, creating a pathway to inclusive growth.
Keywords: O10; O25; O40; O57; P52; 330; Industrial policy; China model; India; inclusive growth; comparative advantage; economic reform